Pengaruh Penggunaan Media Ajar Berbasis Quizizz pada Mata Pelajaran Informatika terhadap Hasil Belajar Siswa Kelas X SMAN 1 Ranah Pesisir - Gusra, Laura Febriani; Asmara, Delvi; Dewi, Ika Parma; Irfan, Dedy (Lembaga Yasin AlSys, 2025)
This study aims to examine the effect of using Quizizz-based instructional media on student learning outcomes in Informatics for Grade X at SMAN 1 Ranah Pesisir. The study is grounded in the need for interactive and engaging learning media to enhance student participation and achievement. A quantitative approach with an experimental design was employed, involving two groups: an experimental group using Quizizz and a control group receiving conventional instruction. Data were collected through a posttest written examination and analyzed using statistical tests to determine significant differences between the two groups. The results show that the experimental class achieved an average score of 87 with a standard deviation of 9.107, while the control class obtained an average score of 77 with a standard deviation of 12.148. Hypothesis testing indicates a positive and significant effect of Quizizz-based media on student learning outcomes. The study concludes that Quizizz-based instructional media are effective in improving learning outcomes and student motivation in Informatics. The findings imply that Quizizz can be utilized as an alternative digital learning medium to support more active, competitive, and enjoyable classroom learning processes.